Helicobacter pylori infection in patients undergoing upper endoscopy at University Hospital in Uberaba, Minas Gerais, Brazil. - Fonseca, Fernanda Machado; Etchebehere, Renata Margarida; Oliveira, Adriana Gonçalves (JMPHC | Journal of Management & Primary Health Care | ISSN 2179-6750, 2013)
<span lang="EN-US" style="font-size: 12.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;">Helicobacter pylori<span lang="EN-US" style="font-size: 12.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA;"> is a Gram negative bacterium that cause chronic gastritis, duodenal ulcers and can predispose the gastric cancer. The study aimed to determinate the prevalence of H. pylori infection by different methods of diagnosis in patients submitted to endoscopy. Of the 145 patients included in the study, were collected fragments of gastric mucosa for histological analysis, and for the rapid urease test. The breath test was also performed. The H. pylori infection was detected in 84 (57.9%) patients by histological study, the rapid test of urease was positive in 81 (55,8%) and the breath test in 62 (56,3%). There was no statistically significant difference when comparing the prevalence of infection by different methods of diagnosis. The prevalence of H. pylori infection in our community was lower than that found in the literature for patients with age similar to this study (mean = 53.19 years).